Strategi Inovasi Pembelajaran Berbasis Nilai Islam untuk Peningkatan Kualitas Pendidikan: Studi Kasus di MI Maarif NU Kaliwangi - Karmiati Karmiati; Sunhaji Sunhaji (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to analyze innovative strategies based on Islamic values to improve the quality of education at This study examines innovative strategies grounded in Islamic values to enhance educational quality at MI Ma’arif NU Kaliwangi. The research addresses a persistent gap between the increasing demands for pedagogical innovation and digital integration in primary education and instructional practices in madrasahs, which remain largely conventional and insufficiently aligned with a systematic internalisation of Islamic values. A qualitative case study design was employed, involving 22 teachers, including the head of the madrasah, and 274 students. Data were collected through in-depth interviews, classroom observations, and document analysis, and analysed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, with validity ensured through source and methodological triangulation. The findings indicate that the implementation of Project-Based Islamic Learning, digital Qur’anic literacy, experiential moral learning, interactive digital media, and the cultivation of digital etiquette significantly enhances students’ learning motivation, Islamic literacy, and character development, particularly in terms of social empathy and learning discipline. The novelty of this study lies in its integrative pedagogical framework that synthesises project-based and technology-enhanced learning with the contextual internalisation of Islamic values at the Islamic primary education level. Theoretically, this research contributes to the advancement of innovation and quality management theories in Islamic education by positioning Islamic values as a pedagogical foundation rather than merely normative content. The implementation is supported by a strong religious culture, adaptive teachers, and parental involvement, although challenges persist regarding infrastructural limitations and uneven technological competence. Continuous teacher professional development and strategic optimisation of educational technology are recommended to sustain innovation in Islamic value-based learning